A differential‐fed dual‐polarized antenna with gain enhancement using hollow dielectric patch resonator. Issue 7 (12th April 2021) - Wang, Xue‐Ying; Tang, Shi‐Chang; Yang, Ling‐Ling; Fang, Hong‐Lian; Chen, Jian‐Xin
Abstract: A differential‐fed dual‐polarized dielectric patch (DP) antenna with high gain, wide bandwidth, and high isolation is investigated in this article. Based on the analysis of the anisotropic property of the DP antenna, further exploration of gain enhancement is carried out. The introduction of the square air hole in the substrate to obtain a hollow DP resonator is a crucial technique. It not only increases the electromagnetic radiation from the sidewalls of the DP resonator to further improve the gain to 8.9 dBi, but also shifts the dominant TM101 mode upward to get close to the higher‐order TM121 mode to achieve bandwidth expansion of 19.4%. By using the differential‐fed scheme to excite the TM101 mode, TM121 mode and their degenerate modes, dual‐polarization operation and high isolation level can be obtained simultaneously.